The effects of interday rest on adaptation to 6 weeks of plyometric training in young soccer players - Ramirez-Campillo, R.; Meylan, C. M. P.; Álvarez-Lepin, C.; Henriquez-Olguin, C.; Martinez, C.; Andrade, D. C.; Castro-Sepúlveda, M.; Burgos, C.; Baez, E. I.; Izquierdo, M. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this study was to determine the effects of short-term plyometric training interposed with 24 or 48 hours of rest between training sessions on explosive and endurance adaptations in young soccer players. A total of 166 players, between 10 and 17 years of age, were randomly divided into 3 groups: a control group (CG; n = 55) and 2 plyometric training groups with 24 hours (PT24; n = 54) and 48 hours (PT48; n = 57) of rest between training sessions. Before and after intervention, players were measured in squat jump, countermovement jump, 20 (RSI20) cm drop jump reactive strength index, broad long jump, 20-m sprint time, 10 × 5-m agility time, 20-m multistage shuttle run test, and sit-and-reach test. The plyometric training program was applied during 6 weeks, 2 sessions per week, with a load from 140 to 260 jumps per session, replacing some soccer-specific drills. After intervention, the CG did not show significant performance changes. PT24 and PT48 groups showed a small-to-moderate significant improvement in all performance tests (p < 0.001), with no differences between treatments. Although it has been recommended that plyometric drills should not be conducted on consecutive days, the study shows that plyometric training applied twice weekly on consecutive or nonconsecutive days results in similar explosive and endurance adaptations in young male soccer players.